2020
DOI: 10.1186/s12872-020-01690-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum N-Acetylneuraminic acid with the risk and prognosis of acute coronary syndrome: a prospective cohort study

Abstract: Background N-acetylneuraminic acid (Neu5Ac) is a functional metabolite involved in coronary artery disease (CAD). We aimed to evaluate the relationship between serum Neu5Ac and the risk and prognosis of acute coronary syndrome (ACS) in a real-world prospective study. Methods Patients with suspected ACS who underwent coronary angiography were included. Serum Neu5Ac was measured at admission. Coronary lesion severity was evaluated by Gensini Score. GRACE risk stratification was performed at admission. Major ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…N -acetylneuraminic acid was associated with myocardial infarction 19 . Given that there were associations between cardiovascular complications and retinal 8 , 20 or renal 7 complication of persons with T2D, N -acetylneuraminic acid could contribute to the shared etiology among the cardiovascular, retinal, and renal complications of persons with T2D.…”
Section: Discussionmentioning
confidence: 97%
“…N -acetylneuraminic acid was associated with myocardial infarction 19 . Given that there were associations between cardiovascular complications and retinal 8 , 20 or renal 7 complication of persons with T2D, N -acetylneuraminic acid could contribute to the shared etiology among the cardiovascular, retinal, and renal complications of persons with T2D.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, Neu5Ac is the most widespread form of sialic acids and is a family of compounds with a broad range of implications in human physiology (30). Because Neu5Ac concentrations have been correlated with the development of cardiovascular disease via RhoA signaling pathway activation (31,32), the fact that we found higher Neu5Ac concentrations associated with COVID-19 provides a new pathway possibly linked to the excess risk of cardiovascular diseases associated with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 68%
“…Browning et al have demonstrated that elevated sialic acid was positively associated with the metabolic syndrome, independent of BMI in women [ 46 ]. Other studies indicate that elevated levels of Neu5Ac during coronary artery disease progression as well as myocardial injury [ 47 , 48 ]. Furthermore, the GALT gene, which is upregulated in OBM, encodes the enzyme galactose-1-phosphate uridylyltransferase, responsible for converting ingested galactose to glucose.…”
Section: Discussionmentioning
confidence: 99%